2020
DOI: 10.15446/innovar.v30n75.83259
|View full text |Cite
|
Sign up to set email alerts
|

The role of leadership styles in organizational citizenship behavior through mediation of perceived organizational support and job satisfaction

Abstract: This paper seeks to examine transformational and transactional leadership, employees’ organizational citizenship behavior, employees’ job satisfaction and perceived organizational sup­port; which are employees' organizational citizenship behavior associations. In addition, this study explores the mediating role of employees’ job satisfaction and perceived organizational support in the relationship between transformational and transactional leadership styles and employees’ organizational citizenship behavior. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 39 publications
1
42
0
2
Order By: Relevance
“…Job satisfaction creates a positive emotional state in the organization that can contribute to social and participatory behaviors ( Zare-Khafri and Hassani, 2014 ). For example, individuals with more job satisfaction in the organization are more likely to display a series of prosocial behaviors similar to OCB ( Asgari et al, 2020 ) and express goodwill and sincerity to customers based on the expectations of the organization because they are expected to repay the organization for treating them well ( Wagner and Hollenbeck, 2010 ). Organ (1988) also indicated that job satisfaction of service providers is an important factor that enhances the citizenship behaviors required to achieve organizational performance, such as helping co-workers and providing additional services to customers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Job satisfaction creates a positive emotional state in the organization that can contribute to social and participatory behaviors ( Zare-Khafri and Hassani, 2014 ). For example, individuals with more job satisfaction in the organization are more likely to display a series of prosocial behaviors similar to OCB ( Asgari et al, 2020 ) and express goodwill and sincerity to customers based on the expectations of the organization because they are expected to repay the organization for treating them well ( Wagner and Hollenbeck, 2010 ). Organ (1988) also indicated that job satisfaction of service providers is an important factor that enhances the citizenship behaviors required to achieve organizational performance, such as helping co-workers and providing additional services to customers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The theory of transformational leadership has been present in many studies and different contexts, some examples are: in the workplace [ 9 ], organizational contexts [ 10 ], crime [ 11 ], and also in the educational field [ 8 ]. It is in the latter context that transformational leadership theory has most recently arrived, giving rise to what it calls “Transformative Teaching” [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the volunteer job could be achieved through OCBs. Absent the collective will to participate; organizations can not improve their effectiveness (Asgari, Mezginejad, & Taherpour, 2019). Individuals with an OCBs act outside their duties and share their strength, ambition and perspective to succeed in the company's interests (Asgari et al, 2019).…”
Section: Literature Review 21 Organizational Citizenship Behavioursmentioning
confidence: 99%
“…Absent the collective will to participate; organizations can not improve their effectiveness (Asgari, Mezginejad, & Taherpour, 2019). Individuals with an OCBs act outside their duties and share their strength, ambition and perspective to succeed in the company's interests (Asgari et al, 2019). Most researchers agree that this factor is multidimensional, and a literature review indicates a lack of consensus on this aspect (Organ, 1988).…”
Section: Literature Review 21 Organizational Citizenship Behavioursmentioning
confidence: 99%